Civil Law Review of Business Contracts in Business Activities - Ratna Dewi; Harry Yusuf Adegdaha Laksana; Ahmad Beny Rias; Adam Damili; Achmad Faried (Jurnal Indonesia Sosial Sains, 2025)
This research addresses the legal framework of business contracts under the Civil Code, focusing on the effectiveness of such contracts in business activities and the consequences of defaults by parties involved. The urgency of this study arises from the increasing complexity and frequency of legal disputes in business transactions, particularly regarding contract breaches. The primary objective is to analyze the legal effectiveness of the Civil Code in resolving defaults and protecting the rights of the involved parties, as well as to evaluate its role in enhancing legal certainty and business trust. The research employs a qualitative descriptive methodology, utilizing document analysis to assess relevant legal provisions and case studies. The findings reveal that the Civil Code provides clear guidelines for the interpretation of contracts, ensuring legal certainty and protection for parties. However, challenges such as cost and time limitations in dispute resolution are evident. In conclusion, the Civil Code plays a crucial role in business contract enforcement, although improvements in flexibility and efficiency are recommended to further support business growth and legal fairness.